Literacy Skills in Medical Education - Yuliana (Proceeding International Symposium on Global Educatiorg Psychology, and Cultural Synergy, 2024)
Literacy skills in medical education are critical to develop competent doctors. There are some literacy skills such as health literacy, information literacy, and critical thinking. This paper aims to describe how literacy skills in medical education can be developed. This is a narrative literature review. Literature was taken from PubMed, Scopus, and Google Scholar, and the publication date was within 10 years. Enhance literacy skills in medical education needs curriculum updates, critical evaluation, and health literacy communication techniques. Health literacy communication skills can be taught by teaching the students how to avoid jargon and give effective questions. Selecting reliable content is the step to critical evaluation. Critical thinking is related to the ability to gather data, reassess, and reanalyze. In conclusion, literacy skills in medical education can be developed by improving the curriculum, training the students to have critical thinking skills, and teaching health literacy communication techniques.